Vernacular Resistance in Mian Muhammad Bakhsh (1830-1907)’s Qissa Saif ul Malook: Language, Authority, and Social Criticism - Anwar, Usman; Perveen, Saima (Pakistan Journal of Humanities and Social Sciences, 2025)
This study presents the work of Mian Muhammad Bakhsh, Saif ul Malook, as a vernacular critique of the misuse of power, linking his spiritual themes with social and moral insights. In this composition, Saif ul Malook, written in simple Punjabi, Mian Muhammad Bakhsh criticizes the Dogra rulers at certain points. Through the use of metaphors in his poetry, he imparts lessons on moral values, empathy, and social justice to the people. By employing simple and common language in his work Saif ul Malook, he conveys an enduring message that encourages patience, coexistence, and standing against social evils.